Motifs of Patriarchal Touches in Meatless Days - Nawaz, Muhammad (International Journal of English Literature and Social Sciences (IJELS), 2019)
Pakistani society is male dominant society and patriarchal values are rife there from time immemorial. Sara Suleri has tried to portray this scenario through her autobiographical book Meatless Days. Though Sara touches the topics of politics, history and culture of Pakistan but motifs of patriarchal touches are rife in this book. Norms of traditions prevalent in Pakistan always favor male member of society. All major feminist concepts favour ideology; where patriarchy, dominance and upper-hand are norms.